Experimental Assessment of the Façade-Integrated Thermoelectric Air-Conditioning Unit towards Development of the Autonomous Curtain Walling Module. (June 2019) - Matuška, T; Zmrhal, V; Zavřel, V; Slanina, P
Abstract: This paper introduces an innovative concept for adaptive wall-curtain façade modules. The façade module integrates functions of heating, cooling, ventilation, lighting, shading as well as renewable energy storage and generation in order to enable autonomous adaptation of each individual façade module to local outdoor and indoor conditions. This paper is focused on the development of the façade-integrated air-conditioning system. Since the wall-curtain façade construction offers only limited space, the solution requires minimalistic size of the air-conditioning system. For this purpose, the application of thermoelectrical cells was investigated and the first prototype of thermoelectrical air-conditioning (mock-up) unit was developed and tested. This paper demonstrates the energy performance of the experimental setup and provides recommendations for further development process.